Central Venous Pressure Measurement Is Associated With Improved Outcomes in Patients With or at Risk for Acute Respiratory Distress Syndrome: An Analysis of the Medical Information Mart for Intensive Care IV Database - Tang, Rui; Peng, Junnan; Wang, Daoxin (Frontiers in Medicine, 2022)
Background: Central venous pressure (CVP) monitoring is widely used in the intensive care unit (ICU). However, the formal utility of CVP measurement to altering patient outcomes among ICU patients with or at risk for acute respiratory distress syndrome (ARDS) has never been investigated. Our study aimed to explore the association of CVP measurement with 28‑day mortality specifically in that population. Methods: This study was based on the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Patients were divided into CVP and no CVP groups according to whether they had CVP measurement within 24 hours of admission to the ICU. The primary outcome was 28-day mortality. Multivariate regression was used to elucidate the association between CVP measurement and 28-day mortality, and propensity score matching (PSM) and propensity score-based overlap weighting (OW) were employed to verify the stability of our results. Results: A total of 10198 patients with or at risk for ARDS were included in our study, of which 4647 patients (45.6%) belonged to the CVP group. Multivariate logistic regression showed that the early measurement of CVP was independently associated with lower 28-day mortality (OR: 0.49; 95% CI: 0.42-0.57; p<0.001). This association remained robust after PSM and OW (both p<0.001). Patients in the CVP group had shorter ICU stay, lower in-hospital mortality, more fluid on day one and higher clearance of blood lactate than those in the no CVP group. Conclusion: Early CVP measurement is associated with an improvement in 28-day mortality among a general population of critically ill patients with or at risk for ARDS.